Stock Market Liquidity and the Long-run Stock Performance of Debt Issuers - Butler, Alexander W.; Wan, Hong (Review of Financial Studies, 2010)
Previous studies document that the stock returns of bond-issuing firms significantly underperform matched peers over the three to five years following issuance. We revisit this phenomenon and show that the underperformance is the result of an omitted return factor (a “bad model problem”). Debt issuers have significantly higher stock market liquidity than size and book-to-market matched counterparts, and differences in liquidity are largest for the worst-performing groups of issuers. When we additionally match on liquidity or when we include a liquidity factor in the model for expected returns, the evidence of underperformance disappears.